PHENOTYPES INVESTIGATION IN THE YEAST SACCHAROMYCES CEREVISIAE ISOLATED FROM DIFFERENT GRAPE CULTIVARS FOLLOWIG FERMENTATION - Bayraktar V.N. (Bìologìčnij Vìsnik Melìtopolʹsʹkogo Deržavnogo Pedagogìčnogo Universitetu Imenì Bogdana Hmelʹnicʹkogo, 2012)
Micobiological investigation was carried out on Saccharomyces cerevisiae yeast cultures, which were isolated from different varieties of vintage grape harvested from the ―Koblevo‖ winery, Nikolaev region of Ukraine. It was determined that wild yeast cultures tend to be of one of three different phenotypes. For comparison and reference, investigation of test cultures was performed with previously known phenotypes and yeast cultures Saccharomyces cerevisiae used in wine industry. It was noted that the most desirable yeast cultures had a killer phenotype. These are able to generate toxins that inhibit the growth of other yeast cultures that are present in the same substrate and compete for habitat. It was observed that yeast a neutral phenotype can also be can also utilized in wine industry biotechnology. Yeast cultures with sensitive phenotype, however, die in the substrate (grape musts) in the presence of yeast culture killer phenotypes that secrete killer toxins harmful to these sensitive phenotypes.